MICROPROBE MONAZITE GEOCHRONOLOGY: PUTTING ABSOLUTE TIME INTO MICROSTRUCTURAL ANALYSIS - Williams M.L.; Jercinovic M.J. (My University, 2002)
High-resolution compositional mapping and dating of monazite on the electron microprobe is a powerful addition to microstructural analysis and an increasingly important tool for tectonic analysis. Microprobe monazite geochronology can be an efficient reconnaissance tool for evaluating metamorphic and deformational age domains, but more importantly, its in-situ nature and high spatial resolution offer an entirely new level of structurally and texturally specific geochronologic data that can be used to put absolute time constraints on P-T-D paths, constrain the rates of metamorphic and deformational processes, and provide new links between metamorphism and deformation. Microprobe geochronology is particularly applicable to three persistent microstructural/microtextural problem areas: (1) constraining the chronology of metamorphic assemblages; (2) constraining the timing of deformational fabrics; and (3) interpreting other geochronological results. Although some monazite generations can be directly tied to metamorphism or deformation, at present, the most common constraints rely on monazite inclusion relations in porphyroblasts that, in turn, can be tied to the deformation and/or metamorphic history. Microprobe mapping and dating allow geochronology to be incorporated into the routine microstructural analytical process, resulting in a new level of integration of time (t) into P-T-D histories.
Keywords: COMPOSITIONAL MAPPING; MICROPROBE MONAZITE GEOCHRONOLOGY; MICROSTRUCTURAL ANALYSIS; TECTONIC ANALYSIS